2013
DOI: 10.1007/s00464-013-2909-4
|View full text |Cite
|
Sign up to set email alerts
|

The multiphasic learning curve for robot-assisted rectal surgery

Abstract: At least three phases in the learning curve for robot-assisted rectal surgery are defined in our study.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
102
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 141 publications
(107 citation statements)
references
References 29 publications
5
102
0
Order By: Relevance
“…They concluded that the learning phase for robotic rectal surgery was achieved after 15 to 25 cases. Similar observations were noted by Jimé-nez-Rodríguez et al and Sng et al [124,125]. While there is no consensus on the exact number of cases required to overcome the learning curve, it is acknowledged that competency with laparoscopic colectomy is recommended prior to operating the robotic system for rectal procedures [126].…”
Section: Colorectal Surgerysupporting
confidence: 61%
“…They concluded that the learning phase for robotic rectal surgery was achieved after 15 to 25 cases. Similar observations were noted by Jimé-nez-Rodríguez et al and Sng et al [124,125]. While there is no consensus on the exact number of cases required to overcome the learning curve, it is acknowledged that competency with laparoscopic colectomy is recommended prior to operating the robotic system for rectal procedures [126].…”
Section: Colorectal Surgerysupporting
confidence: 61%
“…Depending on how the factors were evaluated, this hybrid model reflected surgical success or surgical failure [15,16,18,24,27]. Beyond using time or clinical factors or both to determine the learning curve, several studies compared patient characteristics and outcomes for patients undergoing surgery before and after a portion of the learning curve was overcome [8,13,16,18,20,21,24,25,27,[29][30][31][32].…”
Section: Determination Of the Learning Curvementioning
confidence: 99%
“…Origin: The studies originated from 12 countries; 8 were from the USA [7][8][9][10][11][12][13][14] and 6 from South Korea [15][16][17][18][19][20] with the remainder from a variety of European [21][22][23][24][25][26][27][28] and Asian countries [29][30][31][32].…”
Section: Study Characteristicsmentioning
confidence: 99%
“…72,73 Several reports using CUSUM analytics demonstrated that the learning phase for robotic colorectal surgery consisted of 25-35 cases. [74][75][76] A recent review by Jiménez-Rodríguez et al calculated that the mean number of cases required for a surgeon to be classified as an expert in robotic rectal cancer surgery was 39. 77 In comparison, the learning curve for laparoscopic colorectal surgery varies widely, with an international multicenter analysis by Miskovic et al reporting a range of 88-152 cases.…”
Section: Applicability Of the XI -Overcoming The Learning Curvementioning
confidence: 99%